THE RENAL LESION ASSOCIATED WITH HEMOGLOBINEMIA : II. ITS STRUCTURAL CHARACTERISTICS IN THE RAT - Jaenike, John R. (The Rockefeller University Press, 1966)
Histological studies have been performed on experimental acute renal failure induced by intravenous injection of hemoglobin in rats. These have been correlated with alterations in renal excretory function, assessed by the measurement of inulin clearance, at various stages of the lesion. The most prominent morphological changes during the first 24 hr after hemoglobin injection, when inulin clearance is most markedly suppressed, are: the presence of hemoglobin within the lumen of small intrarenal vessels, particularly the vasa recta; hemoglobin cast formation involving predominantly the thick ascending limbs of the loops of Henle; and evidence of injury of the epithelium of the proximal tubules and thick ascending limbs. Notably absent during this stage of the lesion are marked tubular dilatation, interstitial edema, and cast formation in the distal collecting ducts. The considerable recovery of function which occurs at 72 hr is accompanied by a marked reduction in involvement of the vasa recta. Standard sections and microdissection reveal many markedly dilated proximal tubules at this stage of the lesion, suggesting obstruction of filtering nephrons. These data have led to a tentative hypothesis regarding the pathogenesis of renal failure in this experimental lesion. It is suggested that renal ischemia and failure of glomerular filtration are the primary factors responsible for the early and severe impairment of renal function, and that these are related to intravascular aggregation of hemoglobin pigment. As this defect recedes, tubular obstruction by hemoglobin casts prevents restitution of excretory function in a variable fraction of the nephrons. The latter accounts for the relatively prolonged, moderate reduction in inulin clearance associated with the late stages of this lesion. These hypotheses form the basis for a continuing study of this renal lesion.